1996
DOI: 10.1111/j.1439-0418.1996.tb01596.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Liriomyza trifolii (Burgess) (Dipt., Agromyzidae) on fruit production and growth of tomatoes, Lycopersicon esculentum (Mill) (Solanaceae)

Abstract: The serpentine leafminer, Liriomyza trifolii (Burgess) (Agromyzidae) has, during the past 8 years, become an increasingly important pest on tomatoes, the second most important vegetable crop in South Africa. In some areas where weekly chemical applications are made on the basis of a threshold level of 0.25 mines per plant, it is feared that this pest has become resistant. In the present study, examination of the effect of various levels of infestation on growth and yield of tomatoes showed that neither growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…A further observation with respect to fruit yield also depicted a similar trend with our data that though maximum fruit yield was recorded in abamectin but it was at par with spinosad. Our data observation also had other findings that though there was variation in terms of efficacy against leaf mining activity with each treatment but that could not influence the yield significantly among the treatments and in support, Kotze and Dennill (1996) observed that the phenology of L. trifolii feeding (before or during and after flowering) had no effect and the effect of herbivory by L. trifolii was not obscured by any relationship between fruit production and growth of the tomato plants.…”
Section: Resultssupporting
confidence: 85%
“…A further observation with respect to fruit yield also depicted a similar trend with our data that though maximum fruit yield was recorded in abamectin but it was at par with spinosad. Our data observation also had other findings that though there was variation in terms of efficacy against leaf mining activity with each treatment but that could not influence the yield significantly among the treatments and in support, Kotze and Dennill (1996) observed that the phenology of L. trifolii feeding (before or during and after flowering) had no effect and the effect of herbivory by L. trifolii was not obscured by any relationship between fruit production and growth of the tomato plants.…”
Section: Resultssupporting
confidence: 85%
“…The three Liriomyza species are highly polyphagous, attacking plants in several families 1 (Murphy and LaSalle 1999). Globally, they are important pests of high value horticultural crops such as snow pea (Pisum sativum L.; Fabaceae), French bean (Phaseolus vulgaris L.; Fabaceae), runner bean (Phaseolus coccineus L.; Fabaceae), okra [Abelmoschus esculentus (L.) Moench; Malvaceae], aubergine (Solanum melongena L.; Solanaceae), tomato (Solanum lycopersicum L.; Solanaceae), and passion fruit (Passiflora edulis Sims; Passifloraceae), and they can cause yield losses of up to 100% (Spencer 1973(Spencer , 1990Kotze and Dennill 1996;Chabi-Olaye et al 2008;Gitonga et al 2010). …”
mentioning
confidence: 99%
“…Similarly, leaf miners (mainly Liriomyza species) cause havoc worldwide in a variety of cropping systems (e.g. Spencer, 1972;De Lima, 1979;Singh and Merrett, 1980;Bourdouxhe, 1982;Cardona et al, 1985;ICARDA, 1987;Salas, 1992;Cisneros and Gregory, 1994;Barea et al, 1995;Ujiye and Adachi, 1995;Uygen et al, 1995;Kotze and Dennill, 1996;Singh and Weigand, 1996;Sharaf-El-Din et al, 1997;Cardona et al, 1998;de Souza et al, 1998;Shepard et al, 1998). Stemborers and parasitic weeds (e.g.…”
Section: Developing Biologically Based Ipm Optionsmentioning
confidence: 99%